Pola Interaksi Ruang Kegiatan Usaha Perikanan Tangkap Desa Bajomulyo, Kecamatan Juwana, Kabupaten Pati - Novia Rini Listiana; Djoko Suwandono (Teknik PWK (Perencanaan Wilayah Kota), 2021)
Pati Regency is a regency in Central Java which has abundant natural wealth, one of which is in the potential capture fisheries sub-sector. Capture fisheries business in Pati Regency which is very potential is located in Bajomulyo Village, Juwana District. Bajomulyo Village is synonymous with the term "fishing village" because of the existence of the Bajomulyo Beach Fishing Port as a center for fishing activities. The availability of natural resource wealth developed into a business such as the capture fisheries sub-sector in Bajomulyo Village causes spatial interactions both within the region and with the surrounding area. This is because in the capture fisheries business consists of several units of activity (pre-production, production, post-production) that are interrelated with supply and demand. The capture fisheries business of Bajomulyo Village does not only interact or have local links (within Pati Regency area), but it is related to other areas in pre-production and post-production fishing activities. Business actors who run capture fisheries have been able to optimize the presence of local resources, especially in meeting the needs of supplies and by recruiting local human resources to work in the business. Capture fisheries business in Bajomulyo Village also draws human resources from other regions by providing equal employment opportunities.